Modeling Bureaucratic Simplification to Optimize Service Accessibility in Banten Province during the Industrial Revolution 5.0 Era - Firdaus, Siti Aina; Andayani, Nopi; Ramdhani, Miftah Faiz Ali; Oktaviani, Maya; Zein, Femmy Aryanthi (PINISI Discretion Review, 2025)
This study aims to analyze and develop a bureaucratic simplification model for processing permits for the use of road sections in the Development Work Area (WKP) I of Banten Province during the era of Industrial Revolution 5.0. The main issue addressed is the complexity of licensing procedures that cause service delays, despite the significant potential for revenue generation. Using a descriptive method with a qualitative approach, data were collected through interviews with 13 companies applying for permits. The analysis is grounded in Max Weber's rational-legal theory, which emphasizes the role of formal rules, hierarchy, and division of labor, while also highlighting the need for greater bureaucratic flexibility. The findings reveal that implementing bureaucratic simplification through full digitalization of licensing, system automation, enhanced human resource capacity, technology- and human-centered services, and GPS- and GIS-based monitoring can improve transparency, efficiency, and accountability. Consequently, this model is expected to enhance the public service system in Banten Province, making it more responsive to the needs of communities and business actors in the era of Industrial Revolution 5.0.